G471 Clinical characteristics, laboratory findings and management data in a single-center cohort of patients with heterozygous familial hypercholesterolemia. (25th October 2020) - Elkhateeb, N; Uudelepp, ML; Chakrapani, A; Cleary, M; Davison, J; Footitt, E; Grünewald, S; Batzios, S
Abstract : Background: Familial hypercholesterolemia (FH) is an autosomal dominant lipid metabolism disorder characterized by high blood cholesterol levels and early cardiovascular disease. Patients suffer from either a homozygous or heterozygous form. Heterozygous FH is a common genetic disorder with an incidence of 1:500 people. Patients are normally treated with dietary intervention, statins, bile acid sequestrants, or other lipid-lowering agents. Aim: The aim of this study was to record data to characterize the cohort of heterozygous FH patients in our center. Methods/Case Report: We have retrospectively recorded the epidemiological, clinical, biochemical and genetic data of patients with heterozygous FH aged between 10 and 17 years old treated in our hospital over the last 20 years. In addition, we have recorded data in regards to treatment modalities and biochemical parameters related to response in treatment. Results: We are describing 91 patients with a mean age of 14 years (10–17 years). Fifty-one patients were males and 40 were females. The mean age at diagnosis was 8.9 years (range 1 and 16 years). Most of the patients were asymptomatic at diagnosis, while presentations included associated obesity (8 patients), diabetes mellitus (3 patients), xanthomas and xanthelasmas (1 patient each). Mean levels of total and LDL cholesterol at diagnosis were 6.8 mmol/L (4.2 & 10.1 mmol/L) and 4.7 mmol/L (1.92 & 8.3 mmol/L) respectively. Seventy-seven patients had a positive family history of hypercholesteremia. Forty-two patients had their diagnosis genetically confirmed (mutations in LDLR in 36 patients, and apoB genes in 6 patients respectively). Management included dietary manipulation in 70 patients and pharmacological therapy in 45 patients. Out of various medications, Atorvastatin was the most frequently used in 35 patients. Six months following treatment the vast majority of patients had a favorable outcome with mean levels of total cholesterol and LDL cholesterol being 5.3 mmol/L (3.4–7.9 mmol/L) and 4.37 mmol/L (1.86–6.5 mmol/L) respectively. Conclusion: Our data suggest that familial hypercholesterolemia is a common metabolic disorder and most of the patients are asymptomatic at diagnosis during childhood. A high index of suspicion is required in subjects with a family history of cardiac or cerebrovascular symptoms. Treatment with Statins is effective and early initiation should be considered to avoid long term complications.